Performance of urban climate-responsive design interventions in combining climate adaptation and mitigation - Daniel, Rohan; Cortesão, João; Steeneveld, Gert-Jan; Stremke, Sven; Lenzholzer, Sanda (Building and environment, 2023)
•Urban climate-responsive design interventions assessed quantitatively.•Green infrastructure interventions perform the best regarding climate adaptation.•Solar technology interventions perform the best regarding climate mitigation.•Street scale interventions combine adaptation and mitigation to a larger extent.•Building scale interventions present less synergies than street scale interventions.